Explaining Variation in Parents' and Their Children's Stress During COVID-19 Lockdowns - Toppe, Theo; Stengelin, Roman; Schmidt, Louisa S.; Amini, Naiera; Schuhmacher, Nils (Frontiers in Psychology, 2021)
The coronavirus pandemic poses a substantial threat to people across the globe. During the first half of 2020, governments limited the virus’ spread by imposing diverse regulations. These regulations had a particular impact on families as parents had to manage their occupational situation and childcare in parallel. Here, we examine variation in parents’ and children’s stress during the lockdowns in the first half of 2020 and detect correlates of families’ stress. Between April and June 2020, we conducted an explorative online survey among N = 422 parents of three to ten-year-old children residing in 17 countries. Most participants came from Germany (n = 274), Iran (n = 70), United Kingdom (n = 23), and United States (n = 23). Parents estimated their stress, their children’s stress, and various information on potential correlates (e.g., accommodation, family constellation, education, community size, children’s playtime, contact with peers, media consumption, physical activity). Parents also stated personal values regarding openness to change, self-transcendence, self-enhancement, and conservation. Results indicate substantial variation in families’ stress levels and diverse reactions to regulations. Commonly, children’s media consumption increased compared to the time before the pandemic. Parents raising both preschool-aged and school-aged children were at particular risk of experiencing stress in response to regulations. Estimated stress and reactions varied with children’s age and parents’ personal values, suggesting that such variables need to be considered when implementing and evaluating regulations and supporting young families during the current and future pandemics.